2024
DOI: 10.1002/jvc2.363
|View full text |Cite
|
Sign up to set email alerts
|

Sun protection knowledge, attitudes and practices: A Lebanese‐based survey

Divina Justina Hasbani,
Nohra Ghaoui,
Firas Haddad
et al.

Abstract: BackgroundDespite extensive research on sun protection, there remains a gap in certain populations like Lebanon. It is essential to assess how Lebanese adults handle sun exposure and its risks.ObjectivesTo examine the knowledge and habits of sun protection use among adults in Lebanon and explore the possible association between a history of skin cancer or photo‐related disorder and sun protection behaviours.MethodsWe conducted a single‐centre cross‐sectional study on 1001 patients presenting to the American Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(45 reference statements)
1
0
0
Order By: Relevance
“…There were no significant increases of odds with a history of skin cancer, and using sunscreens observed among the patient groups in the current study is an interesting finding that warrants further exploration. A recent study in Lebanon found a similar pattern [ 31 ]. This suggests that the relationship between KAP constructs may be more complex, particularly in certain populations, and requires deeper investigation.…”
Section: Resultssupporting
confidence: 65%
“…There were no significant increases of odds with a history of skin cancer, and using sunscreens observed among the patient groups in the current study is an interesting finding that warrants further exploration. A recent study in Lebanon found a similar pattern [ 31 ]. This suggests that the relationship between KAP constructs may be more complex, particularly in certain populations, and requires deeper investigation.…”
Section: Resultssupporting
confidence: 65%